The Effect Of Self Efficacy, E-Commerce And Accounting Information Systems On The Decision Of Accounting Program Alumni Of Universitas Palangkaraya To Become Entrepreneurs - Emanuela, Anggi Indriany; Ludigdo , Unti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Entrepreneurship is one of the solutions for problems regarding unemployment, a widely- -discussed issue in Indonesia. Entrepreneurial intention nowadays can be fostered earlier, making new entrepreneurs from younger generations appear. The process of becoming an entrepreneur is affected by both internal and external factors. As the internal one comes from the individuals themselves, the external one is the individuals’ surrounding environments. E-commerce provides much ease and more advantages than the conventional concept of trade since the former enables information to be procured quicker and more completely without being limited by time and place. An accounting information system is a data processing tool for information seekers. This research aims to identify the effects of self-efficacy, e-commerce, and accounting information systems on how alumni of the accounting program of Universitas Palangkaraya make their decision to become entrepreneurs. This study uses primary data, which was harvested from questionnaires and analyzed using multiple linear regression. The results indicate that self-efficacy, e-commerce, and accounting information systems positively affect the decision to become entrepreneurs.